Human papillomavirus (HPV) type distribution in cervical carcinoma, low-grade, and high-grade squamous intraepithelial lesions in Venezuelan women - Correnti, Maria; Medina, Francisco; Cavazza, María Eugenia; Rennola, Antonieta; Ávila, Maira; Fernándes, Andreína (Gynecologic oncology, 2011)
Cervical cancer is an important cause of mortality among women in developing countries, especially in the Latin America and Caribbean (LAC) region. Infection with high-risk (HR) human papillomavirus (HPV) has been identified as the primary cause of cervical cancer. The aim of this study was to determine the frequency of HR-HPV genotypes in low-grade and high-grade squamous intraepithelial lesions (LSIL, HSIL) and cervical carcinoma (CC) among Venezuelan women. Subjects with histopathological diagnosis of LSIL, HSIL, and CC (LSIL = 200; HSIL = 100; CC = 150) were enrolled in the study after obtaining informed consent. Biopsy samples of these subjects were analyzed to determine the lesion type. HPV detection and typing was done using polymerase chain reaction (PCR) and reverse hybridization. HPV type specific prevalence was determined in subjects with single and multiple infections. HPV DNA was detected in 68%, 95%, and 98.7% of LSIL, HSIL, and CC cases, respectively. HR-HPV and low-risk oncogenic HPV (LR-HPV) was observed in 66.9%/11.8% of LSIL cases, 87.3%/3.2% of HSIL cases, and 91.2%/0.7% of CC cases. HPV types -16/-18 (65%) were the most common high-risk HPV types observed, followed by types -52, -33, -45, and -31. Cervical cancer burden in Venezuelan women is substantial. HPV types -16/-18 were the most common types prevalent among Venezuelan women followed by types -52, -33, -45, and − 31 (prevalence, ~ 90.1%). The results of this study provide baseline information on the HPV type distribution, which may facilitate the development of a cervical cancer prevention and control program in Venezuela. ►This study is the first comprehensive study conducted in Venezuela that investigated the distribution of HPV types in LSIL, HSIL, and CC lesions. ►HPV-16/-18 were the most common types prevalent among Venezuelan women followed by types -52, -33, -45, and -31 (prevalence, ~ 90.1%). ►The results of this study provide baseline information on the HPV type distribution, which may facilitate the development of a cervical cancer prevention and control program in Venezuela.